ВЫЧИСЛЕНИЕ ОПРЕДЕЛЕННОГО ИНТЕГРАЛА МЕТОДОМ МОНТЕ-КАРЛО С ПРИМЕНЕНИЕМ TURBO PASCAL - Шульгина-Таращук, А.С.; Беляева, Л.Н. (Изд-во КарГУ, 2009)
Мақалада Turbo Pascal программасын қолданып анықталған интегралды есептеу үшін Мон- те-Карло əдісі қарастырылады. Ол əдіс кездейсоқ шамаларды модельдеу əдісі ретінде таны- мал. Бұл əдісті теориялық-ықтималдық сипаттау есептерінде қолданады, себебі əдістерінің дамуына ықпалын тигізеді. Method Monte-Carlo is considered in article at calculation of the certain integral with use the program Turbo Pascal. The method Monte-Carlo possible to define as method of modeling of the random quantities for the reason calculations of the features of their distribution. This method has rendered and continues to render the essential influence upon development of the methods computing mathematicians and at decision of the many tasks successfully matches with other computing methods and complements them. Its using justified in the first place in that task, which allow the theoristprobabilistic description.